(untitled) (Marketing Journal, 2025)
This article presents ideas and considerations on the priority areas of state regulation of investment projects, namely, improving the living standards of the population in the country by further increasing the scale of investments, creating new jobs, incr easing economic growth rates, widely implementing innovative ideas and technologies, and creating a competitive environment in the economy.